Návrh marketingového řízení firmy - Dojmazov, Petr (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Cílem této diplomové práce je analýza současného stavu komunikační agentury Aetna spol. s r.o. a následné navržení vhodné marketingové strategie, která by měla zajistit úspěšný rozvoj firmy a její uplatnění na trhu komunikačních agentur. Zvláštní důraz byl kladen na analýzu současného stavu a na základě jejího vyhodnocení byla stanovena nová vize a nový směr, kterým by se agentura měla ubírat, tak aby obstála v konkurenčním boji i v budoucnu.

The goal of this diploma thesis is the analysis of current situation of communication agency Aetna, s.r.o., and following suggestion of a suitable strategy, which should provide successful development of the company and its implementation in the market of communication agencies. The emphasis was put especially on the analysis of the current situation and on the basis of its evaluation, new vision and new direction for the agency to follow in order to be successful and competitive even in the future.
The Proposal of Marketing Management of Company
Keywords: Strategie; Marketing; Management; Komoditní trh; Strategy; Marketing; Management; Commodity Market